Studies of laccase from Trametes versicolor in aqueous solutions of several methylimidazolium ionic liquids - Alberto Domínguez (2011)
Stability and kinetic behavior of laccase from Trametes versicolor in the presence of several ionic liquids from the methylimidazolium family have been investigated. In general laccase stability diminished as the size of the alkylic substitute in the methylimidazolium ring increased. Higher concentrations of ionic liquids caused more destabilization than lower ones. Thus, low concentrations of [C(2)mim(+)][EtSO(4)(-)] allowed maintaining enzymatic stability. [C(4)mim(+)][Cl(-)] appeared to have a stabilizing effect on laccase, as little activity decay was observed within three weeks. Kinetic studies indicated that both [C(2)mim(+)][EtSO(4)(-)] and [C(4)mim(+)][Cl(-)] inhibited laccase activity, although 10-fold more [C(2)mim(+)][EtSO(4)(-)] than [C(4)mim(+)][Cl(-)] was required to cause the same degree of inhibition. A kinetic model was developed to represent the experimental data.